The Effect of Cystamine on Acute Radiotoxicity of P32 in Mice - Mewissen, D. J.; Comar, C. L. (Nuklearmedizin - NuclearMedicine, 1961)
A total of 240 DBA I mice were given one intraperitoneal injection of P32. The experimental group was given a 0.2 percent aqueous solution of cystamine for a 60-day period as drinking water; controls received only ordinary water. The protective effect of cystamine per os against the radiotoxicity of P32 was statistically significant.The L. D. 50/30 days was estimated 4.5 μc/gm for the control group and 6.1 μc/gm for the cystamine group.The biological half-life of P32 in DBA I mice was estimated to be 8.1 days.A 9-percent retention out of the initial dose, corrected for physical decay, was found in DBA I mice after a 3-month period.Deux series totalisant 240 souris DBA I reçurent une injection intra-péritonéale de P32. Le groupe témoin reçut de l’eau ordinaire comme boisson. Le groupe expérimental reçut une solution de 0.2% de Cystamine pendant 60 jours.L’action protectrice de la Cystamine “per os” vis à vis du pouvoir létal du P32 fut significative.Dans le groupe contrôle la D. L. 50/30 jours fut estimée à 4,5 μc/g et dans le groupe protégé à 6.1 μc/g.La demi-vie biologique du P32 chez ces souris fut estimée à 8.1 jours.Une rétention de 9% de la dose intiale, pourcentage corrigé pour la demi-vie physique, subsistait après 3 mois chez les souris DBA I.Zwei Serien von insgesamt 240 Mäusen DBA I erhielten eine intraperitoneale Injektion von P32. Die Vergleichsgruppe erhielt gewöhnliches Wasser zum Trinken. Die Versuchsgruppe erhielt eine Lösung von 0,2% Cystamin für die Dauer von 60 Tagen.Die Schutzwirkung des Cystamins peroral gegenüber der Radiotoxizität des P32 war signifikant.In der Kontrollgruppe wurde die DL 50/30 Tage zu 4,5 μC/gm bestimmt und in der geschützten Gruppe zu 6,1 μC/gm.Die biologische Halbwertszeit des P32 wurde bei den Mäusen DBA I mit 8,1 Tagen bestimmt.Eine Retention in Höhe von 9% der Ausgangsdosis, korrigiert für die physikalische Halbwertszeit, wurde nach 3 Monaten bei den DBA-Mäusen gefunden.